ANALYSIS OF FORWARD CHAINING METHOD ON LAPTOP DAMAGE DIAGNOSIS EXPERT SYSTEM - Jufri, Fikri Ramadhan; Akbar, Muhamad Rafi; Auriga, Wira; Syaputra, Eka Benny (Jurnal Sistem Informasi dan Ilmu Komputer, 2024)
The forward chaining method is used in expert systems to reach conclusions by starting from known facts and moving forward to find a solution or diagnosis. In diagnosing damage to student laptops, this method will begin with information about the symptoms or problems experienced by the computer laptop. The system will evaluate these symptoms and match them with pre-programmed rules to identify possible causes of damage. This process continues by adding new information and making decisions based on sequentially applied rules until reaching a final diagnosis. In diagnosing damage to student laptops, the forward chaining method can help systematically identify problems based on observed symptoms, guiding users through the diagnosis process efficiently. Keywords: forward chaining, expert systems, laptop damage.